Mini Review: Logistic, Ditribution and Procurement - Fasida Dharma Yudastoro (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the study to see whether these three variables already exist that discuss quantitatively or qualitatively, will also be presented scientific articles related to the three variables above the research method used is a literature review derived from existing scientific articles from various journals in the world related to variables. The results of research whose perspective the researcher does not exist directly state the results with certainty are only the perspective of previous authors and add strongly to the results of previous research.